SUN-255 The Synthetic Progestin, 17-alpha-hydroxyprogesterone Caproate, Used in Human Pregnancy Alters Prefrontal Cortical Development in Rats - Lolier, Melanie L (J Endocr Soc, 2020)
17-alpha-hydroxyprogesterone caproate (17-OHPC) is a synthetic progestin commonly prescribed for the prevention of recurrent preterm birth. Treatment with 17-OHPC in high-risk pregnant women begins between gestational weeks 16-20, and continues through week 36 (1). Recent studies suggest that 17-OHPC is not an effective treatment for reducing rates of preterm delivery (2,3). Most concerning is the timing of 17-OHPC administration, which coincides with critical periods of mesocortical dopamine pathway development in the fetus (4). Regulating behaviors of executive function, the mesocortical pathway originates in dopaminergic neurons of the ventral tegmental area (VTA) that innervate the medial prefrontal cortex (mPFC). Disruptions in mesocortical dopamine pathway development are believed to underlie deficits in cognitive functioning (5,6). In rodent models of cortical development, the developing mesocortical dopamine pathway is sensitive to progestins. There is transient expression of nuclear progesterone receptors (PR) in both the VTA and mPFC (7). PR are powerful transcription factors that can alter gene expression and fundamentally alter neural development (8,9). When rodents are treated with 17-OHPC during mesocortical dopamine pathway development, there are significant sex-specific alterations in dopaminergic innervation of the mPFC and deficits in cognitive behaviors in adulthood (10). Microglia, the resident immune cells of the central nervous system, play a critical role in establishing dopaminergic circuitry of the forebrain (11). The following experiment tested the hypothesis that 17-OHPC alters microglia activity in a sex-specific manner. Our results reveal that there is an innate sex difference in the number of reactive microglia, where control group females had significantly more than males. Treatment with 17-OHPC abolishes this sex difference by reducing the number of reactive microglia in 17-OHPC treated females to male-like levels in both the prelimbic (PL) and infralimbic (IL) mPFC. There is also a significant reduction in the percentage of reactive microglia in 17-OHPC treated animals compared to controls. These results suggest that early 17-OHPC exposure may decrease functional microglial activity during critical periods of cortical development, and that females are more vulnerable than males. Consideration should be given to the potential effects of 17-OHPC on neural and cognitive development in children.